Generalized Lobs Theorem Strong Reflection Principles and Large Cardinal Axioms Consistency Results in Topology - Foukzon, Jaykov (Journal of Asian Scientific Research, 2017)
In this article we proved so-called strong reflection principles corresponding to formal theories Th which has omega-models.